Differentiation plasticity of human monocytes in culture - Bojan Joksimović; Sergej Tomić; Marina Bekić; Miloš Vasiljević; Dragana Vučević; Miodrag Čolić (Биомедицинска истраживања, 2020)
Introduction: Human monocytes are heterogeneous and plastic cell population with the ability to undergo phenotypic and functional changes as a response to a stimulus from a local microenvironment. Our aim was to determine the potential of human monocytes to differentiate into different cell populations depending on two different cytokines (IL-4 and IL-6) added to cultures as well as to compare their phenotypical and functional characteristics. Methods: Peripheral blood mononuclear cells (PBMNC) were isolated from buffy coats of healthy donors. Monocytes, which were separated from PBMNC by plastic adherence, had been cultivated in Dendritic cell (DC), serum free medium for 5 days, either with granulocyte/macrophage colony-stimulating factor (GM-CSF) alone or with GM-CSF, with addition of interleukin 4 (IL-4) or interleukin 6 (IL-6), respectively. After cultivation, phenotypic characteristics of these cells were analyzed by flow cytometry, whereas the levels of produced cytokines in culture supernatants were quantified by ELISA. The potential of differentiated cells to modulate the proliferation of allogeneic T cells was examined by co-cultivation of these cells with PBMNC. Results: GM-CSF differentiated monocytes into M0/M1 macrophages (MØ). The combination of GM-CSF and IL-4 favoured differentiation of immature DC, whereas GM-CSF and IL-6 transformed monocytes into monocytic myeloid derived suppressor cells (M-MDSC). All cell populations expressed typical monocyte/macrophage markers such as CD14, CD11b, CD16 and CD33, HLA-DR, CD209 and CD86, a co-stimulatory marker. DC and M-MDSC expressed CD1a and CD11c, in contrast to M0/M1 MØ. The expression of HLA-DR, CD1a, CD209 and CD86 was highest on DC. The expression of CD33 and CD16 was highest on M-MDSC, followed by lowest expression of HLA-DR. The potential of promoting T-cell proliferation was highest in cultures of PBMNC with DC, whereas M-MDSC had the opposite, suppressive, effect. These differences correlated with highest production of immunosuppressive cytokines such as IL-10, IL-27 and TGF-b by M-MDSC. Conclusion: This study confirmed the differentiation plasticity of human monocytes, which are influenced by cytokines added in cultures. Phenotypic characteristics of these cells correlated with the production of cytokines involved in modulation of T-cell proliferation.
Keywords: plasticity; differentiation; monocytes; culture; cytokines; T cell proliferation